2009
DOI: 10.1007/s11433-009-0238-3
|View full text |Cite
|
Sign up to set email alerts
|

The change of magnetic inclination angles associated with the X3.4 flare on December 13, 2006

Abstract: Recent studies showed a consistent pattern of changes in the sunspot structure associated with major flares: part of the peripheral penumbral regions vanishes during flares, and meanwhile, the umbral cores and/or inner penumbral regions are darkened. To understand the underlying physics of these observations, we compare the magnetic inclination angle in the decayed peripheral and the enhanced inner penumbral regions before and after the 4B/X3.4 flare of 2006 December 13 by using the highresolution vector magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
6
16
0
Order By: Relevance
“…Namely, the transverse field near the magnetic polarity inversion line (PIL) at the core flaring region is enhanced rapidly and irreversibly, which is often accompanied by an increase of magnetic shear. Such a rapid change of vector PMFs closely associated with flares/CMEs has been consistently found later on using ground-based (Schmieder et al 1994;Wang et al 2002Wang et al , 2004bWang et al , 2005Wang et al , 2007Liu et al 2005;Su et al 2011) and Hinode observations (Jing et al 2008;Li et al 2009). Indirect evidence includes the unbalanced flux evolution of the line-of-sight magnetic field , the variation of the sunspot white-light structure in flaring regions (Wang et al 2004a;Deng et al 2005;Liu et al 2005;Chen et al 2007), and the change in the pattern of the penumbral Evershed flow (Deng et al 2011).…”
Section: Introductionsupporting
confidence: 58%
“…Namely, the transverse field near the magnetic polarity inversion line (PIL) at the core flaring region is enhanced rapidly and irreversibly, which is often accompanied by an increase of magnetic shear. Such a rapid change of vector PMFs closely associated with flares/CMEs has been consistently found later on using ground-based (Schmieder et al 1994;Wang et al 2002Wang et al , 2004bWang et al , 2005Wang et al , 2007Liu et al 2005;Su et al 2011) and Hinode observations (Jing et al 2008;Li et al 2009). Indirect evidence includes the unbalanced flux evolution of the line-of-sight magnetic field , the variation of the sunspot white-light structure in flaring regions (Wang et al 2004a;Deng et al 2005;Liu et al 2005;Chen et al 2007), and the change in the pattern of the penumbral Evershed flow (Deng et al 2011).…”
Section: Introductionsupporting
confidence: 58%
“…For example, a large increase in inclination angle for ROI 1 (Figure 3(d)) between the second and third scans is accompanied by a slight increase in field strength (Figure 3(a)), giving approximately no change in the horizontal field (Figure 3(b)). The Li et al (2009) result supports the reconnection picture of Liu et al (2005), whereby newly connected fields near the magnetic neutral line contributed to field inclination becoming more horizontal. This picture suggests that the field lines after the flare in our study become newly reconnected, low-lying, more horizontal field lines near the flaring neutral line.…”
Section: Discussionsupporting
confidence: 74%
“…Li et al (2009) also found a transverse-field increase of 20% after an X3.4 flare. We found no significant changes in transverse-field strength either immediately before or after the flare.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The authors interpret the sudden change of penumbral white light structure to be a result of the change of overall magnetic field inclination down to the photosphere due to magnetic reconnection in the flare, which was then confirmed by other authors (Sudol & Harvey 2005;Li et al 2009). …”
Section: Introductionmentioning
confidence: 53%